Mental healthcare in paediatric epilepsy clinics: implementation by non-mental health professionals - Roz Shafran; Tamsin Ford; Sophie Bennett; Isobel Heyman; Rona Moss-Morris; Anna E Coughtrey; Peter Fonagy; J Helen Cross; Emma Dalrymple; Poonam Jetha; Cameo Stanick; Bruce Chorpita; et al. (BMJ Paediatrics Open)
Objectives Research has shown that children with epilepsy often experience mental health disorders but face barriers to effective care. One solution is to train healthcare professionals within paediatric epilepsy services to deliver psychological interventions. The aim of this paper was to examine aspects of treatment integrity of the ‘Mental Health Interventions for Children with Epilepsy’ (MICE) treatment, a modular cognitive behavioural therapy intervention for anxiety, depression and behavioural difficulties in childhood epilepsy.Methods The MICE treatment was delivered in paediatric epilepsy clinics by 21 healthcare professionals with limited mental health experience, supported by a comprehensive training and supervision package. Data from 2269 treatment sessions with 166 young people were analysed to examine adherence to the MICE protocol. Audio recordings from a randomly selected sample of 251 sessions were rated for therapist competence, of which 30 were independently rated by a second expert.Results Therapists administered the MICE intervention with integrity and closely adhered to the established protocol. Any adaptations made were related to the sequence of delivery rather than changes to the content.Conclusions The overall findings indicate that professionals in paediatric epilepsy clinics can be effectively trained and supported to administer evidence-based mental health interventions. Additional research is required to explore the link between integrity and clinical outcomes, as well as to determine the most effective methods for training and supervision. This is crucial for ensuring the successful implementation of mental health interventions for children with epilepsy and concurrent mental health needs.